Synergistic effect of polysaccharides and flavonoids on lipid and gut microbiota in hyperlipidemic rats. Issue 2 (20th December 2022) - Bai, Yun-fei; Yue, Zhi-Liang; Wang, Ya-nan; Li, Yan-dong; Li, Chong; Liu, Xin-tong; Shi, Ruo-han; Huo, Ning-ning; Li, Dan-dan; Gao, Shan; Han, Xue
Abstract : HDC interventions prevent hyperlipidemia by regulating intestinal microbiota and lipid absorption and metabolism in the intestine, and have a synergistic effect. Abstract : Hyperlipidemia is a global health risk factor, and its development is closely related to the absorption and metabolism of lipids in the intestine. In this study, the Auricularia auricula polysaccharide, the Tremella polysaccharide, and hawthorn flavonoids were mixed by equal weight (HDC), and then its effect on the intervention in the intestine and blood lipids of hyperlipidemic rats on a high-fat diet (HFD) was investigated. The results revealed that HDC significantly inhibited the development of hyperlipidemia and reduced lipid levels and fat accumulation. In addition, HDC improved the edema deformation of intestinal epithelial cells, impaired the intestinal barrier induced by HFD, and improved the antioxidant capacity of the intestine. HDC showed a significant synergistic effect. Analysis of the gut microbiota by 16s rRNA gene sequencing showed that HDC reduced the ratio of Bacteroidetes / Firmicutes and the relative abundance of actinomycetes . At the genus level, the relative abundance of Lactobacillus, Rumincococcaceae-UCG-14, and Muribaculaceae was increased and the relative abundance of Allobaculum, Corynebacterium-1, Blautia, and Turicibucter was decreased. Intestinal lipidomics showed that HDC reduced the levels of DGDG, LPE, PG, phSM, PIP2, SoG1, and SM in the intestine of HFD rats, although there were no significant differences in LPE, PG, and phSM. 42 HDC-acting lipid biomarkers were screened. In conclusion, these findings support the potential of HDC intervention to prevent hyperlipidemia by regulating gut microbiota and lipid absorption and metabolism in the intestine.